Exercise and Sleep during Adolescence: Examining the Effects of Different Types of Physical Activity on Sleep Quality - Shabani Ezdini, Esmail; Faraeen, Maryam (KMAN Counseling & Psychology Nexus, 2025)
This narrative review aimed to examine the effects of different types of physical activity—including aerobic exercise, resistance training, mixed modal routines, and team sports—on sleep quality in adolescents. A narrative review approach with descriptive analysis was employed to synthesize empirical studies published between 2020 and 2025. Relevant articles were retrieved from databases such as PubMed, Scopus, Web of Science, and PsycINFO using keywords related to adolescent sleep, physical activity types, and sleep quality indicators. Studies were selected based on inclusion criteria focusing on adolescents aged 10 to 19 years and examining sleep outcomes such as latency, duration, and efficiency. The data were thematically categorized by type of physical activity and analyzed to identify patterns, mechanisms, and moderating or mediating variables influencing the relationship between movement and sleep. The review found consistent evidence that physical activity positively influences adolescent sleep across all activity types. Aerobic exercise was associated with shorter sleep latency and improved duration through thermoregulatory and circadian mechanisms. Resistance training enhanced sleep efficiency and slow-wave sleep via anabolic recovery processes. Mixed modal activities, such as high-intensity interval training, yielded synergistic effects on sleep due to their integration of aerobic and strength components. Team and competitive sports offered both physical and psychosocial benefits, improving emotional regulation and routine stability. In contrast, sedentary behavior and excessive screen time were linked to delayed sleep onset, poor sleep efficiency, and increased fragmentation. The influence of physical activity on sleep was moderated by gender, chronotype, and exercise timing, and mediated by factors such as emotional regulation and academic stress. Engaging in regular, appropriately dosed physical activity is a practical and effective strategy to enhance sleep quality in adolescents. Tailored interventions considering individual differences and lifestyle factors are essential for optimizing outcomes.